Use of computed tomography as a non‐invasive method for diagnosing cephenemyiosis in roe deer (Capreolus capreolus). Issue 1 (8th October 2014) - FIDALGO, L. E.; LÓPEZ‐BECEIRO, A. M.; VILA‐PASTOR, M.; MART ÍNEZ‐CARRASCO, C.; BARREIRO‐VÁZQUEZ, J. D.; PÉREZ, J. M.
Abstract This study was conducted to assess the reliability of computed tomography (CT) for diagnosing bot fly infestations by Cephenemyia stimulator (Clark) (Diptera: Oestridae) in roe deer (Capreolus capreolus L.) (Artiodactyla: Cervidae). For this purpose, the heads of 30 animals were analysed, firstly by CT and then by necropsy, which was used as the reference standard method. The prevalence values obtained by both methods were identical; the prevalence of infestation was 40.0% overall, and was higher in males (45.5%) than in females (25.0%). These results highlight the usefulness of CT as an alternative or non‐invasive method for diagnosing cephenemyiosis in live‐captured roe deer and in hunting trophies or museum collections that cannot be destroyed or damaged.